Humor and Critical Literacy: Exploring Stand-Up Comedy in Indonesian Language Education - Azizah, Aisyah Nimatul; Maharani, Putri (Jurnal Tahuri, 2025)
This study investigates the potential of stand-up comedy as a pedagogical strategy for enhancing critical literacy in Indonesian language classrooms. Unlike conventional literacy practices that emphasize technical reading and writing skills, stand-up comedy offers a space for students to combine humor, performance, and critique. Using a qualitative case study at a public senior high school in Indonesia, data were collected through classroom observations of student performances, interviews with teachers and students, and textual analysis of students’ written monologues. The findings show that stand-up comedy enables students to transform everyday experiences into critical commentary, express social critique in accessible and creative forms, and develop confidence in public speaking. Humor proved effective in stimulating reflective dialogue on sensitive issues, fostering peer engagement, and encouraging students to negotiate meanings beyond the textbook. The novelty of this study lies in positioning stand-up comedy as a form of multimodal literacy that integrates text, performance, and humor, highlighting its role as both linguistic practice and critical pedagogy. Challenges were identified in guiding humor responsibly, particularly when addressing sensitive or controversial topics. This research demonstrates the value of integrating popular culture into literacy education to cultivate students’ critical, contextual, and creative capacities.